2007
DOI: 10.1007/s10120-006-0408-1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic resection of early gastric cancer

Abstract: The purpose of this review is to examine recent advances in the techniques and technologies of endoscopic resection of early gastric cancer (EGC). Endoscopic mucosal resection (EMR) of EGC, with negligible risk of lymph node metastasis, is a standard technique in Japan and is increasingly becoming accepted and regularly used in Western countries. EMR is a minimally invasive technique which is safe, convenient, and effi cacious; however, it is insuffi cient when treating larger lesions. The evidence suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
521
2
23

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 620 publications
(553 citation statements)
references
References 78 publications
7
521
2
23
Order By: Relevance
“…When histological evaluation was difficult, or, revealed that a lesion was outside the indication criteria and/or that it had a positive margin, the curability was defined as noncurative hospital stay (on post-ESD day 10). The complication rate (bleeding and perforation) was similar to those in other reports [2][3][4][5][6][7][8][9][10], showing that ESD was mostly safely performed even in the elderly. Curative ESD was achieved in 366 of 470 lesions (77.9%).…”
Section: Early Outcomessupporting
confidence: 87%
See 1 more Smart Citation
“…When histological evaluation was difficult, or, revealed that a lesion was outside the indication criteria and/or that it had a positive margin, the curability was defined as noncurative hospital stay (on post-ESD day 10). The complication rate (bleeding and perforation) was similar to those in other reports [2][3][4][5][6][7][8][9][10], showing that ESD was mostly safely performed even in the elderly. Curative ESD was achieved in 366 of 470 lesions (77.9%).…”
Section: Early Outcomessupporting
confidence: 87%
“…Endoscopic submucosal dissection (ESD) is widely recognized as a safe and effective treatment of EGC [2][3][4][5], even in aged or high-risk patients [6][7][8][9][10]. However, little information is available on the long-term outcomes of ESD in a large number of elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26] All patients were inhabitants from around the Wakayama area. In Japan, where the incidence of gastric cancer is high, treatment of mucosal gastric cancer without lymph node metastasis is usually achieved with endoscopic resection, preserving the stomach.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Although institutional differences in indications for endoscopic resection exist, lesions with preoperative endoscopic diagnoses of intestinal-type intramucosal cancer without ulcer findings, intestinal-type intramucosal cancer 3 cm in diameter with ulcer findings and intestinal-type minute invasive submucosal (<500 lm below muscularis mucosa) cancer 3 cm in diameter are considered to be indicated for endoscopic resection. 25,26 In these 267 patients, the extent of coexisting CAG was evaluated endoscopically and by the results of 2 serum tests, pepsinogen (PG) and H. pylori antibody level, as described in the following section.…”
Section: Study Subjectsmentioning
confidence: 99%
“…ER is indicated for tumors with a negligible risk of lymph node (LN) metastasis [6]. Although the indications for ER specifi ed by the Japanese treatment guidelines are strictly limited to small mucosal tumors with differentiated histology (D-type), expanded indications for some D-type lesions (intramucosal cancers either ≀3 cm in size with no lymphatic-vascular capillary involvement regardless of ulceration fi ndings or with no ulceration regardless of tumor size) have been proposed and accepted by high-volume ER centers [2,6,7].It remains in dispute, however, as to which undifferentiated-type (UD-type) EGC lesions involve a negligible risk of LN metastasis. We recently published a study in which 3843 cases of surgically resected UD-type EGCs were examined, with particular emphasis placed on investigating the existence of LN metastasis [8].…”
mentioning
confidence: 99%